Konflik Pekerjaan dan Keluarga pada Pasangan dengan Peran Ganda - Wongpy, Novensia; Setiawan, Jenny Lukito (Jurnal Psikologi Teori dan Terapan, 2019)
Work-family interface can be viewed from two directions, work-to-family and family-to-work. The imbalance in carrying out two roles in the area of work and family will trigger conflict, which is known as work-to-family conflict and family-to-work conflict. The aim of this study was to compare work and family conflicts in working husbands and wives. The participants were 30 married couples (60 persons) who have one child and work as employees, managers and entrepreneurs. Work-family conflict was measured using a questionnaire that measures the level of conflict in two directions, work-to-family conflict and family-to-work conflict. The result shows that there is no difference in work-to-family conflict between husbands and wives. However, there is difference between work-to-family conflict and family-to-work conflict with the average of work-to-family conflict is higher than family-to-work conflict for both husbands and wives. The findings indicate that gender difference does not affect the ways in balancing between work and family roles among both husbands and wives. Keywords: Work-family conflict, family-work conflict, dual career couple Abstrak: Work-Family Interface dapat ditinjau dari dua arah yaitu work-to-family dan family-to-work. Ketidakseimbangan dalam menjalankan dua peran di area pekerjaan dan keluarga akan memicu konflik yang disebut sebagai work-to-family conflict dan family-to-work conflict. Penelitian ini bertujuan untuk membandingkan konflik pekerjaan dan keluarga pada pasangan suami dan istri yang keduanya bekerja. Subjek penelitian adalah 30 pasangan suami istri (60 orang), minimal telah memiliki satu anak dan bekerja sebagai karyawan, manager maupun wiraswasta. Work-family conflict diukur dengan menggunakan angket tertutup yang mengukur level konflik dari dua arah yaitu work-to-family conflict dan family-to-work conflict. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan work-family conflict antara kelompok suami dan kelompok istri. Namun, terdapat perbedaan antara work-to-family conflict dan family-to-work conflict dengan nilai rata-rata work-to-family conflict lebih tinggi dibandingkan dengan family-to-work conflict baik pada kelompok suami maupun istri. Penelitian ini menunjukkan tidak ada perbedaan gender dalam cara menyeimbangkan peran dalam pekerjaan dan rumah tangga.